1991
DOI: 10.1111/j.1365-2621.1991.tb01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative changes in bacteria, amino acids and biogenic amines in sardine (Sardina pilchardus) stored at ambient temperature (25–28°C) and in ice

Abstract: Summary Freshly caught sardines contained high levels of bacteria located mainly on the skin and the gills. These bacteria invaded and grew rapidly in sardine muscle, reaching 5x108 c.f.u. g‐1 and 6x108 c.f.u. g‐1 respectively after 24h at ambient temperature and 8 days in ice. Histidine, arginine, lysine, tyrosine and methionine levels decreased during storage. The other amino acids, except proline and taurine, accumulated in the fish muscle, indicating an extensive proteolysis. Histamine, cadaverine and putr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 17 publications
(23 reference statements)
1
31
2
2
Order By: Relevance
“…In general, the concentration of histidine, lysine and tyrosine decreased after 12 h stored at ambient temperature. Similar result was also found in sardine (Ababouch et al 1991) and fish sauce (Zaman et al 2011). In contrast, free amino acids were reported to increase during storage in dry-cured grass carp (Zhang et al 2011).…”
Section: Amino Acidssupporting
confidence: 81%
See 1 more Smart Citation
“…In general, the concentration of histidine, lysine and tyrosine decreased after 12 h stored at ambient temperature. Similar result was also found in sardine (Ababouch et al 1991) and fish sauce (Zaman et al 2011). In contrast, free amino acids were reported to increase during storage in dry-cured grass carp (Zhang et al 2011).…”
Section: Amino Acidssupporting
confidence: 81%
“…Wendakoon et al (1990) found correlation between amino acids and biogenic amines, whereas, RuizCapillas and Moral (2004) only correlated histamine concentration to that of histidine concentration, other amines were not correlated to its corresponding amino acid. Other authors reported the absence of such correlation (Ababouch et al 1991;Antoine et al 2002;Ruiz-Capillas and Moral 2002). The profile of biogenic amines in fish is also influenced by the type of microbial flora found in the aquatic environment.…”
Section: Introductionmentioning
confidence: 95%
“…The TABC in the muscle of fish in our study was lower than that the TABC of 3 9 10 4 , 10 5 , and 8.7 9 10 4 cfu g -1 (Ababouch et al 1991;Lakshmanan et al 2002;Manju et al 2007) found in some tropical fish and enumerated at 28-37°C. However, the bacterial load found in muscle in our study did not agree with that of Kim et al (2001) who rarely found bacteria in the muscle of Pacific Mackerel.…”
Section: Total Bacteria In Different Body Parts Of the Fishcontrasting
confidence: 79%
“…However, in some cases formation of toxic amounts of HI in pelagic fish stored in ice have been reported. 17,37 Moreover, some relationship between HI and enterobacteria development was found. In fact, levels of HI were negligible before enterobacteria counts reached 10 5 cfu g −1 , which are the minimum counts reported to be able to produce significant amounts of HI.…”
Section: Biogenic Amine Production During Ice Storagementioning
confidence: 99%